The Effect of Goods Security and Tracking System On Customer Satisfaction of PT J&T Express East Jakarta - Mohammad Fatih Fatih; Aufa Akmal Maulana; Edhiye Budi Setiawan (Dinasti Review, 2025)
This study aims to empirically analyze the influence of goods security and tracking systems on customer satisfaction in J&T Express customers in Indonesia. Amid the mushrooming of online shopping habits, every e-commerce company is competing to get customers, as many companies are trying various strategies to attract customers, such as the development of tracking system features and the security of goods delivery, which is expected to increase customer satisfaction. Methods This research uses a quantitative descriptive method, with the analysis tool used being SEM-PLS (Structural Equation Model-Partial Least Square) Smart PLS 4.0 software. With a total of 120 respondents taken by purposive sampling. This study shows that the tracking system affects the safety of goods and customer satisfaction, and the safety of goods during delivery also affects customer satisfaction, The results of this study indicate that the safety of goods and tracking systems have a significant effect on customer satisfaction, as evidenced by the results of the Discriminant Validity test, Direct Effect test, Indirect Effect test and Goodness of Fit Test which show that variables Tracking System and Safety of Goods have a significant effect because the test results prove their influence on variable Customer Satisfaction.